Brown child the best of the Faigao poetry and fiction, 1984-2012 - Kintanar-Alburo, Erlinda; Yu, Hope Sabanpan (University of San Carlos Press and Cebuano Studies Center, 2013)
Collection of Cebuano poetry and fiction from the Cornelio Faigao Memorial Annual Writers workshops from 1984 to 2012.